Metode Pembelajaran pada Mata Pelajaran Matematika di Kelas III MI Al Athfaliyah Rejosari Grobogan - Suffah, Fella; Kinesti, Rakanita Dyah Ayu (YASIN, 2025)
This study is motivated by the limited research on mathematical learning difficulties among third-grade students at Madrasah Ibtidaiyah, particularly concerning the role of engaging and Islamic-value-based teaching approaches in enhancing interest, motivation, and fundamental mathematical understanding. The objective is to analyze the factors influencing learning difficulties in mathematics and to measure the effect of implementing an engaging teaching approach on students’ interest and comprehension in mathematics at MI Al Atfaliyyah. Employing a qualitative case study method, the research involved 27 purposively selected students identified as having learning difficulties. Data collection techniques included in-depth interviews, participatory observation, and documentation of students’ learning outcomes, which were analyzed using thematic analysis and pattern matching. The findings reveal that engaging and contextual teaching approaches positively correlate with increased student interest and understanding in mathematics. The primary factors causing learning difficulties were weak mastery of basic concepts and mathematical formulas, alongside monotonous teaching methods. These results align with constructivist theory and contextual learning approaches emphasizing the active role of students in building understanding. The study concludes that integrating Islamic values into innovative mathematics teaching approaches is essential for creating enjoyable and meaningful learning experiences for Madrasah Ibtidaiyah students. The implications include enriching theoretical literature and the need for developing teaching strategies more relevant to the characteristics of madrasah learners.